1876-1877 N.C. Sess. Laws 162-63 - (:unkn) unknown (My University, 1876)
ch. 104, § 1: Prohibited the concealed carry of any pistol, Bowie-knife, dirk, dagger, slung-shot, loaded cane, brass knuckles, iron knuckles, or other deadly weapon of a like kind. Violators guilty of a misdemeanor.
Keywords: CARRY - CONCEALED